BELF vs L1 in communication during cross border collaboration project activities - Ina Suryani, Ab Rahim; Rozilawati, Mahadi; Sharmini, Abdullah (Universiti Malaysia Perlis (UniMAP), 2009)
Organized by Centre for Communication Skills and Entrepreneurship (UniMAP), 5-6 December 2008 at The Legend Hotel, Kuala Lumpur.